DMP-1 expression in alveolar bone socket following Anredera cordifolia (Ten.) Steenis treatment: A histological study (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The study aimed to ascertain how Anredera cordifolia (Ten.) Steenis Gel affects the expression of protein dentin matrix protein-1 (DMP-1) in alveolar Wistar rats after tooth extraction.Materials and Methods: Rats were given A. cordifolia (Ten.) Steenis gel was in the socket after tooth extraction, and then the wound was sutured. The rats were sacrificed for 8 and 15 days following tooth extraction. The results on the 8th and 15th days demonstrate that the expression of DMP-1 in the treatment group is significantly higher than in the control group.Results: Expression of DMP-1 in the socket after tooth extraction on days 8 and 15 with a 400x magnification light microscope in both of the A. cordifolia (Ten.) Steenis gel treatment groups showed significant differences compared to the control group.Conclusion: The use of A. cordifolia (Ten.) Steenis gel can stimulate DMP-1 expression in alveolar bone after tooth extraction.Adv. Vet. Anim. Res., 11(2): 291-295, June 2024http://doi.org/10.5455/javar.2024.k775